Recruitment of women veterans into suicide prevention research: Improving response rates with enhanced recruitment materials and multiple survey modalities - Gaeddert, Laurel A.; Schneider, Alexandra L.; Miller, Christin N.; Monteith, Lindsey L.; Brenner, Lisa A.; Katon, Jodie; Hoffmire, Claire A. (Research in nursing & health, 2020)
Women veterans (WV) are the fastest growing veteran subpopulation and recognized to be at increased risk for suicide compared with civilians. Improving engagement (e.g., response rates) of WV in survey research is critical to ensuring valid and generalizable findings, which can inform suicide prevention programs tailored for this population. Many factors are known to influence response rates, yet little is known about ways to optimize survey response rates among WV. Three recruitment cohorts (Waves 1 [W1], 2a [W2a], and 2b [W2b]) of WV were invited to participate in an online survey for a national, mixed‐methods study examining suicide risk among WV using reproductive health care services paid for or provided by the Veterans Health Administration. To examine the effects of enhanced recruitment efforts, standard recruitment materials were mailed to all three cohorts, with the additions of: a study flyer aiming to build trust between participants and researchers (W2a, W2b) and a paper survey (W2b). Characteristics of responders and non‐responders were compared by wave and across survey modalities. Response rates were significantly higher for groups receiving enhanced (W2a = 17.1%; W2b = 24.6%) versus standard (W1 = 12.2%) recruitment materials. WV residing in rural areas were significantly more likely to respond by paper (37.1%) than online (19.8%). Non‐respondents were disproportionately racial and ethnic minorities. Disclosure of sensitive information (e.g., military sexual trauma) did not differ by survey modality. Findings suggest that enhanced recruitment materials improve survey response rates among WV, an important consideration for future research with this population.